THE STAGES OF DEVELOPING COMMUNICATIVE COMPETENCE IN THE PROCESS OF TEACHING FOREIGN LANGUAGES. - Rakhmonqulova Dilshoda Murodkuziyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the stages of developing communicative competence in foreign language teaching. It emphasizes the importance of communicative competence as a core objective in language education, outlining a systematic approach that teachers can adopt to enhance students’ language skills. The stages discussed include awareness, practice, application, and assessment, each playing a crucial role in fostering effective communication abilities. The article aims to provide educators with practical strategies to implement these stages in their teaching practices.